A Comparison of Preparation Times between Manual, Rotary, and Reciprocating Files in Primary Molar Pulpectomy - Ilana Middleton; Martin Vorster; Peet J. van der Vyver (Wolters Kluwer Medknow Publications, 2024)
Aim: To compare preparation times using manual, rotary, and reciprocating files during pulpectomy treatment of primary molars. Settings and Design: This study was an in vitro, randomised, cross-sectional study. Methods: The study was performed on 60 extracted human primary mandibular second molars. Only mesiobuccal canals were prepared using one of three preparation techniques; each preparation technique group comprised 20 canals. Canal preparations were performed by a single, skilled operator using stainless-steel (ss) K-files (ISO size 20-35), a ProTaper Gold SX file, and a WaveOne Gold Medium file following glide path preparation. Preparation times were recorded in second (s) with a digital stopwatch. Statistical Analysis: Preparation times were compared using analysis of variance and the Kruskal-Wallis analysis of variance, where appropriate. The level of significance was set at P ≤ 0.05. Results: The mean preparation time using the ss K-files was significantly longer (186.4 s) than when using the ProTaper Gold SX (29.6 s) or WaveOne Gold Medium files (30.5 s) (P < 0.001). Similar preparation times were recorded when using the ProTaper Gold SX and WaveOne Gold Medium files (P = 0.939). Conclusion: Preparation times with the ProTaper Gold SX and WaveOne Gold Medium files were significantly faster than when using the ss K-files to prepare primary tooth root canals for pulpectomy. Similar preparation times were noted when using the rotary and reciprocation instrumentation groups (P > 0.05).